THE LANGUAGE INTERFERENCE IN ENGLISH SPEAKING ABILITY FOR EFL LEARNERS - Dedy Subandowo (Universitas Negeri Padang, 2017)
This paper examines the language interference on speaking English. The interference was influenced by the mother tongue of the learners. Therefore, this study explains the forms of language interference in speaking ability and the factors are affecting the language interference. In addition, the study attempts to use case study with descriptive qualitative research approach. The data were collected by using the questionnaire and recording technique. The data, then, were analyzed based on the students ‘sounds that have been recorded. The data were formulated in table illustrating the spread of the students’ interference. In identifying the students’ sounds, three classifications of the English pronunciation were applied. The result shows that most of the students made error in their pronunciation, 2% of consonants / tʃ / and / ʒ / and 3% of vowel /u/. The sound production of students did many mistakes in their pronunciation started from consonant to vowel sounds. The mistakes in consonant sounds caused by the mother tongue were highly interfered. The pronunciation in manner of articulation occurred in consonants such as,/p/, /t/, /d/, /k/, /g/ in plosive and /m/ in nasal. Moreover, for the place of articulation, the mistakes appeared on /θ/ and /ð/ in dental and /ʒ/ and /ʃ/ palate-alveolar. The factors influencing mother tongue interference to the students‟ pronunciation are the environment, students’ motivation, and its sound dynamics.